Preparation, Characterization, and Application of P(aluminum chloride-co-diallyldimethylammonium chloride) Hybrid Flocculant - Xinrui Feng; Bei Liu (Applied Sciences, 2024)
The hybrid flocculant P(aluminum chloride-co-diallyldimethylammonium chloride) was synthesized in this study. Diallyldimethylammonium chloride monomers were used and ammonium persulfate served as the initiator. The structure of P(aluminum chloride-co-diallyldimethylammonium chloride) was characterized using Fourier-transform infrared spectroscopy, scanning electron microscopy, an electrical conductivity test, and thermogravimetric analysis. Single-factor experiments were conducted to optimize the synthetic conditions of the hybrid flocculant. An optimized product with an intrinsic viscosity of 926.36 mL/g and a flocculation decolorization rate of 99% was obtained under the following reaction conditions: the total monomer concentration was 30%, the initiator concentration was 0.7%, the reaction temperature was 60 °C, and the reaction time was 3 h. The results demonstrated that the PAC-PDMDAAC hybrid flocculant exhibited covalent bonding between its organic–inorganic components and displayed enhanced stability properties due to its high intrinsic viscosity and spatial structure. Moreover, this hybrid flocculant showed superior decolorization performance in disperse-violet-H-FRL-dye wastewater.